Early and very early‐onset schizophrenia compared with adult‐onset schizophrenia: French FACE‐SZ database. Issue 2 (7th January 2020) - Coulon, Nathalie; Godin, Ophélia; Bulzacka, Ewa; Dubertret, Caroline; Mallet, Jasmina; Fond, Guillaume; Brunel, Lore; Andrianarisoa, Méja; Anderson, George; Chereau, Isabelle; Denizot, Hélène; Rey, Romain; et al.
Abstract: Objective: To compare the clinical symptomatology in patients with Early‐Onset Schizophrenia (EOS, N = 176), especially the subgroup Very Early Onset Schizophrenia (VEOS) and Adult Onset Schizophrenia (AOS, N = 551). Method: In a large French multicentric sample, 727 stable schizophrenia patients, classified by age at onset of the disorder, were assessed using standardized and extensive clinical and neuropsychological batteries: AOS with onset ≥ 18 years and EOS with onset < 18 years (including 22 VEOS < 13 years). Results: The importance of better diagnosing EOS group, and in particularly VEOS, appeared in a longer DUP Duration of Untreated Psychosis (respectively, 2.6 years ± 4.1 and 8.1 years ± 5.7 vs. 1.0 years ± 2.5), more severe symptomatology (PANSS Positive And Negative Syndrome Scale scores), and lower educational level than the AOS group. In addition, the VEOS subgroup had a more frequent childhood history of learning disabilities and lower prevalence of right‐handedness quotient than the AOS. Conclusion: The study demonstrates the existence of an increased gradient of clinical severity from AOS to VEOS. In order to improve the prognosis of the early forms of schizophrenia and to reduce the DUP, clinicians need to pay attention to the prodromal manifestations of the disease. Abstract : To describe schizophrenia from childhood to adulthood is complex and patients with early‐onset schizophrenia (EOS) remain undiagnosed or misclassified, especially the subgroup with very early‐onset schizophrenia (VEOS). In patients with VEOS, the DUP which exceeds 8 years, almost eight times higher than in patients with AOS, objective the problem of early diagnosis and the need to develop diagnostic programs and management cares.